ANALISIS MOTIVASI DAN KINERJA PENGAWAS SEKOLAH DI SEKOLAH DASAR KECAMATAN ABIANSEMAL KABUPATEN BADUNG - I Wayan Arka (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2019)
on. Creating quality human resources, then all managers and teams of educational devices must be able to work professionally and sustainably. School Supervisors are authorized to conduct education supervision in schools by carrying out assessment and coaching in terms of technical education and administration at education units at the preschool, elementary and secondary levels. Efforts to create good and conducive teaching and learning situations are not denied by various negative factors that arise by inhibiting the process of achieving the goals set. To ensure its quality, the education process must be monitored. Analyzing the motivation and performance of school supervisors is very important to improve the quality of teaching of teachers in improving the quality of student learning. Based on the results of research on the analysis of motivation and performance of elementary school supervisors in the Abiansemal District shows that it is not optimal, so that it can make recommendations to the Government as a policy maker to build competent and professional school supervisors in carrying out their duties as educational supervision.Keywords: Motivation, Performance, School Superintendent